Controlling the selectivity to chemicals from lignin via catalytic fast pyrolysis - Ma, Zhiqiang; Troussard, Ekaterina; van Bokhoven, Jeroen A. (Applied catalysis. A, General, 2012)
Selective conversion of lignin to chemicals via catalytic fast pyrolysis. [Display omitted] ► Selective conversion of lignin to chemicals via catalytic fast pyrolysis is described. ► The influence of acidity, pore size, and zeolite structure was determined. ► A reaction pathway of lignin non-catalytic/catalytic fast pyrolysis was proposed. The catalytic fast pyrolysis of alkaline lignin to useful chemicals was investigated using zeolite catalysts with different acidity and pore size. The catalyst played dual roles in this process. In its acid form, it catalytically converted the depolymerized intermediates into desirable and more stable products. This and their surface prevented repolymerization and coke formation. The yield of liquid and the selectivity to desired products can be controlled by tuning of the acidity and pore size of the catalyst. Using no catalyst yielded 40wt.% of liquid, which mainly consisted of 6wt.% (carbon yield) of phenols and 19wt.% (carbon yield) of phenol alkoxy species. The highest yield of phenol alkoxy species was obtained over H-ZSM5 of extremely low number of acid sites; liquid yield of 51wt.% and carbon yield of 24wt.%. The highest yield of liquid (75wt.%) was obtained over H-USY, which had the largest pore size and lowest Si/Al ratio, thus the largest number of acid sites among all the catalyst tested; the carbon yield of aromatic hydrocarbons was around 40wt.% at 650°C. Depolymerized lignin products undergo consecutive reaction to form phenol alkoxy, phenols, and eventually aromatic hydrocarbons.